2022
DOI: 10.3389/fphar.2022.938447
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Our Understanding of the Mechanism of Action of Drugs (including Traditional Chinese Medicines) for the Intervention and Treatment of Osteoporosis

Abstract: Osteoporosis (OP) is known as a silent disease in which the loss of bone mass and bone density does not cause obvious symptoms, resulting in insufficient treatment and preventive measures. The losses of bone mass and bone density become more severe over time and an only small percentage of patients are diagnosed when OP-related fractures occur. The high disability and mortality rates of OP-related fractures cause great psychological and physical damage and impose a heavy economic burden on individuals and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 195 publications
(190 reference statements)
0
9
0
Order By: Relevance
“…In China, MQEF is used for the treatment of postmenopausal osteoporosis and non-traumatic femoral head necrosis and has received positive responses ( 28 ). The use of MQEF is based on Chinese medical theory and lacks modern pharmacological studies.…”
Section: Discussionmentioning
confidence: 99%
“…In China, MQEF is used for the treatment of postmenopausal osteoporosis and non-traumatic femoral head necrosis and has received positive responses ( 28 ). The use of MQEF is based on Chinese medical theory and lacks modern pharmacological studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently used mainly for back pain caused by osteoporosis and is included in the Chinese osteoporosis treatment guidelines. It has various pharmacological activities, such as anti-inflammatory, anti-aging, and estrogenic properties ( 11 , 36 ). Although MQEP has been used in China for more than 1,300 years, its mechanism of action is still unclear and is only explained based on TCM theories; its clinical use relies more on the experience of TCM doctors.…”
Section: Discussionmentioning
confidence: 99%
“…The modified Qing’ e Pills (MQEP) is an herbal compound used in China for over a thousand years and as a complementary treatment for primary osteoporosis with good clinical efficacy ( 11 ). Some studies have shown that MQEP can improve bone microstructure and biomechanics in ovariectomized osteoporosis models, and this effect is achieved by increasing β-catenin protein expression ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the combination of drugs with different mechanisms may bring additional benefits 264 . Furthermore, the sequential use of drugs can avoid the increased risk of specific side effects and minimize the resistance caused by the long‐term use of a single drug 265 . However, it is not recommended to use two anti‐absorbent agents at the same time because of the excessive inhibition of bone turnover and increased risk of fracture 266 …”
Section: Anti‐osteoporosis Therapiesmentioning
confidence: 99%